BULLYING IN SCHOOLS: ACTION AND VICTIMIZATION - Karine Bueno do Nascimento; Marilia de Rosso Krug; Fátima Terezinha Lopes da Costa; Bianca Bueno do Nascimento (Editora da Universidade de Santa Cruz do Sul, 2013)
This study aimed to examine the prevalence of bullying victims, their behavioral characteristics and the associated feelings of public school students. This is why the issue has drawn the attention of teachers across the country, and this work is a way to contextualize the daily lives of students on this aspect. For this, we used the questionnaire from English institution Kidscape, as having interviewed 459 students of both sexes, enrolled from 5th to 8th grade in three public schools in the city of Cruz Alta-RS. Through the data obtained, it can be seen that bullying is present in the local schools, with the reflection unmotivated students to attend the school environment because of these daily abuses, among many other aspects discussed in the study. Given this, it is necessary engagement of the school community and by the state public policies aimed at the topic at hand.